Integration of soil solarization with soil amendments, botanicals and microbial pesticides for the management of soil-borne diseases of strawberry - RAJ, HARENDER (Indian Phytopathology, 2014)
Treatment combination of soil solarization with different amendments, were either applied before solarization (neem cake or neem granules or cauliflower leaves or leaves/seed of five local plants) or after solarization (Trichoderma viride, Pseudomonas florescence) for management of soil borne diseases of strawberry. Among these, combination of soil solarization with transparent polyethylene mulch (25 Âµm thick) for 40 days with soil amendment of neem cake was found most effective and statistically at par in efficacy with treatment combination of soil solarization and root dip of strawberry runners and drenching with Saaf (0.2%) in reducing the combined incidence mainly comprising of crown rot (Rhizoctonia solani), southern blight (Sclerotium rolfsii) and wilt (Fusarium oxysporum f. sp. fragariae) by 96.2% in comparison to unsolarized control. This treatment also resulted up to 70.6% increase in plant height, 72.4% in root length, 176.4% in number of runners per plant, 148.8% in average fruit weight and 108.7% in yield per hectare in comparison to control. Other treatment combinations of soil solarization with soil amendments applied before soil solarization were also found statistically at par. Treatment combinations of soil solarisation with the two microbial bio-pesticides were found slightly less effective.Â